Controllable Galvanic Synthesis of Triangular Ag–Pd Alloy Nanoframes for Efficient Electrocatalytic Methanol Oxidation. Issue 24 (29th April 2015) - Xu, Lin; Luo, Zhimin; Fan, Zhanxi; Yu, Sijia; Chen, Junze; Liao, Yusen; Xue, Can
Abstract Triangular Ag–Pd alloy nanoframes were successfully synthesized through galvanic replacement by using Ag nanoprisms as sacrificial templates. The ridge thickness of the Ag‐Pd alloy nanoframes could be readily tuned by adjusting the amount of the Pd source during the reaction. These obtained triangular Ag–Pd alloy nanoframes exhibit superior electrocatalytic activity for the methanol oxidation reaction as compared with the commercial Pd/C catalyst due to the alloyed Ag–Pd composition as well as the hollow‐framed structures. This work would be highly impactful in the rational design of future bimetallic alloy nanostructures with high catalytic activity for fuel cell systems.